Why and How Do Prison Litigation Strategies and Their Cultures Matter? - Cliquennois, Gaëtan (The British journal of criminology, 2025)
This article highlights the main impediments and inequalities in access to justice for prisoners. Access to justice is considered by European institutions to be one of the vehicles for transforming legislation for better respecting human rights. However, we show that the nature and intensity of strategic litigation depend on three main prison litigation models. These models differentially impact access to justice for prisoners through three main obstacles—deterrence, procedural obstacles and legal aid. Hence, by forging the concept of differentiated litigation, this article calls attention to the different ways in which prison litigation is carried out on the ground and how these lead to different impacts on the barriers to access to justice.